Analysis of cytopathologic examination and hybrid capture in women receiving care in basic health units - Ströher, Deise Jaqueline; Aramburu, Thaís Delgado Brandolt; Nunes, Vinícius Tejada; Piccoli, Jacqueline da Costa Escobar; Manfredini, Vanusa (Brazilian Journal of Sexually Transmitted Diseases, 2016)
Introduction: Cervical cancer is one of the most frequent cancers among Brazilian women and its relationship with the human papillomavirus (HPV) is well established. Objective: To analyze the presence of DNA/HPV using Hybrid Capture method for women in the city of Uruguaiana (RS). Methods: During the period of January to December 2015, 51 cervicovaginal samples were collected from patients who sought care at Basic Health Units in the city. After the collection, conventional and liquid-based cytological analysis was performed. Results: The results of the study indicate the prevalence of genital HPV infection in 5.9% of the samples; low-risk DNA/HPV was detected in 3.9% of patients of reproductive age (PIR); and 2.0% of PIR presented highrisk DNA/HPV. By stratifying the prevalence of HPV in age, we found positivity between 16 and 31 years. Conclusion: Conventional cytology is often inconclusive and, in such cases, using molecular biology methods that detect the DNA/HPV presence would be very useful.